A laboratory infrastructure for flexible automation and integrated manufacturing research. (1st January 2000) - Chen, F. Frank; Saygin, Can
Technical innovations within the scopes of manufacturing, electronics, and information technologies constantly change the existing software and hardware infrastructure of computer integrated enterprises. The increasing emphasis on the CIM systems necessitates continuous improvement and upgrade of the research and educational missions of university manufacturing research laboratories, in accordance with the latest developments in the field of computer technology and its related manufacturing applications. With the intent to provide a laboratory flexible manufacturing cell mimicking major features of most industrial flexible manufacturing systems (FMS) for university research and educational use, the Flexible Manufacturing Systems Laboratory at the University of Toledo has been established. This paper introduces the basic features and capabilities of this laboratory in conjunction with a synopsis of research projects being undertaken and those being planned for.